2023
DOI: 10.3390/su151410951
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Characteristics of an Innovation Team and Collaborative Innovation Performance: The Mediating Role of Cooperative Behavior and the Moderating Role of Team Innovation Efficacy

Mi Zou,
Peng Liu,
Xuan Wu
et al.

Abstract: Based on the theory of social cognition, this paper discusses the cognitive characteristics of an innovation team, the influence mechanism of cooperative behavior on collaborative innovation performance, and the moderating effect of team innovation efficacy in an enterprise collaborative innovation network. The hypothesis has been verified on the basis of 288 valid questionnaires. The results show the following: in the process of collaborative innovation, different dimensions of innovation team cognitive chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…This theory elucidates the mechanisms through which individuals engage in self-regulation, employing control and reinforcement strategies to attain a desired behavior in the pursuit of a long-term objective [23,27]. Ten [28], Zou et al [29], and the authors of [30] identified SCT as one of the most significant frameworks for comprehending and explaining risky behaviors. SCT provides a valuable theoretical framework for describing how people acquire and sustain behavioral patterns, especially addictive behaviors [31].…”
Section: Literature Review 21 Social Cognitive Theory (Sct)mentioning
confidence: 99%
“…This theory elucidates the mechanisms through which individuals engage in self-regulation, employing control and reinforcement strategies to attain a desired behavior in the pursuit of a long-term objective [23,27]. Ten [28], Zou et al [29], and the authors of [30] identified SCT as one of the most significant frameworks for comprehending and explaining risky behaviors. SCT provides a valuable theoretical framework for describing how people acquire and sustain behavioral patterns, especially addictive behaviors [31].…”
Section: Literature Review 21 Social Cognitive Theory (Sct)mentioning
confidence: 99%